FORMULASI JUS DBOG PISANG KEPOK MUSA PARADISIACA L SEBAGAI JUS ANTIOBESITAS - Sutanta sutanta; Habid Al Hasbi; Lailatul Badriah (Sekolah Tinggi Ilmu Kesehatan Estu Utomo Boyolali, 2024)
Background: Food consumption is very easy to obtain and various types of packaging that do not pay attention to the nutritional content, causing obesity. Obesity is a problem that must be controlled immediately because it has bad impacts, including hypertension, diabetes mellitus, kidney failure and other diseases. Dbog Banana Kepok Musa Paradisiaca L is very easy to obtain in areas of Indonesia, especially in the fostered village area Metuk village. From the results of laboratory analysis of Dbog Banana Kepok Musa Paradisiaca L, triterpenoid compounds were obtained. Seeing these results, researchers are interested in conducting research on the effect of consuming Dbog Banana Kepok Musa Paradisiaca L on obesity. Objective: To determine the effect of consuming boiled Dbog Banana Kepok Musa Paradisiaca L on weight loss. Method: This study is a quasi-experimental study with a sample of 23 respondents. Data processing was carried out using SPSS to obtain the results of the Wilcoxon signed rank test. Results: The results of the bivariate analysis showed significant results that there was an effect of giving boiled Dbog Banana Kepok Musa Paradisiaca L on weight loss with a significance result of 0.001 (p <0.05) which means that HO was rejected and Ha was accepted Conclusion: There is an effect between giving boiled Dbog Banana Kepok Musa Paradisiaca L on weight loss Keywords: formulation, dbog Musa Paradisiaca L, antiobesity